WHEN DISCIPLINE MEETS TECHNOLOGY: THE DUAL EFFECT OF GADGET USAGE AND STUDY HABITS ON STUDENT LEARNING - Fitria, Dea; Faslah, Roni; Wolor, Christian Wiradendi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to determine the effect of gadget use and learning discipline on the learning outcomes of tenth-grade students at SMKN 25 Jakarta. This study was conducted using a quantitative approach with a survey method. Data was collected through a questionnaire distributed via Google Forms and analyzed using multiple linear regression. The analysis results indicate that: gadget usage has a positive and significant effect on academic performance, study discipline has a positive and significant effect on academic performance, simultaneously, gadget usage and study discipline have a significant effect on academic performance. These findings confirm that gadgets can be an effective learning tool if used wisely, and academic discipline is a key factor in achieving academic success. Therefore, schools and parents need to guide students to use technology wisely and cultivate a disciplined attitude toward learning.